Pengaruh Dimensi Kualitas Pelayanan Terhadap Kepuasan Konsumen Pada Bali Komputer Di Tenggarong - Syahruddin Syahruddin (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2022)
Abstract :Computer Bali is a business of selling laptops, computers and computer parts in the city Tenggarong addressed in Jalan Danau Aji No: 41 RT.8 Malay Village Tenggarong District with the owner named Agus Alwardana S.Pd. In an effort to improve customer satisfaction the steps taken is to maximize the quality of service to consumers with the maximum number of employees Discussion on simultaneous hypothesis is proven that the quality of service in Bali Computer in Tenggarong a significant effect on the level of consumer satisfaction. These results have hinted that the dimensions of quality of service consisting of reliability, responsiveness, assurance, empathy and tangible can not be separated separately so that the necessary harmony between the five variables in order to maintain and improve customer satisfaction Bali Computer in Tenggarong better. thus the hypothesis that the variable service quality has a significant influence on customer satisfaction in Bali Computer Tenggarong accepted and proven true Discussion of the hypotheses that have been proposed that partially proved the hypothesis was accepted as a whole because each variable can influence consumer satisfaction in Bali Computer Tenggarong. Individually variable five variables consisting of reliability, responsiveness, assurance, and tangible empahty have a significant influence on the increase in customer satisfaction. it is thus suspected of variable reliability that have the most dominant effect on customer satisfaction in Bali Computer in Tenggarong rejected and unsubstantiated.Keywords: Service, Satisfaction